2007
DOI: 10.1523/jneurosci.3209-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

A WAVE-1 and WRP Signaling Complex Regulates Spine Density, Synaptic Plasticity, and Memory

Abstract: The scaffolding protein WAVE-1 (Wiskott-Aldrich syndrome protein family member 1) directs signals from the GTPase Rac through the Arp2/3 complex to facilitate neuronal actin remodeling. The WAVE-associated GTPase activating protein called WRP is implicated in human mental retardation, and WAVE-1 knock-out mice have altered behavior. Neuronal time-lapse imaging, behavioral analyses, and electrophysiological recordings from genetically modified mice were used to show that WAVE-1 signaling complexes control aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
192
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(210 citation statements)
references
References 52 publications
18
192
0
Order By: Relevance
“…Previous studies showed that WAVE1 is highly localized to dendritic spines (47). WAVE1 KO neurons had decreased dendritic spine density, suggesting a role for WAVE1 in dendritic spine formation (4,47). In the current study, we also observed lower baseline dendritic spine density in WAVE1 D1-KO MSNs compared with WT MSNs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies showed that WAVE1 is highly localized to dendritic spines (47). WAVE1 KO neurons had decreased dendritic spine density, suggesting a role for WAVE1 in dendritic spine formation (4,47). In the current study, we also observed lower baseline dendritic spine density in WAVE1 D1-KO MSNs compared with WT MSNs.…”
Section: Discussionsupporting
confidence: 78%
“…Accumulating evidence indicates that adaptive cocaine action involves potentiation of glutamatergic afferents arising from mPFC, amygdala, and ventral hippocampus preferentially onto D1-MSNs (41-44), although D2-MSNs still contribute to certain behavioral features of cocaine action (45,46). Previous studies showed that WAVE1 is highly localized to dendritic spines (47). WAVE1 KO neurons had decreased dendritic spine density, suggesting a role for WAVE1 in dendritic spine formation (4,47).…”
Section: Discussionmentioning
confidence: 99%
“…The WRC triggers N-WASP-dependent activation of actin-related protein (Arp)-2/3-dependent actin nucleation 57,58 , which controls actin filament rearrangements connected to dendritic spine formation, retraction, motility, structure and stability 59 . Disturbing WRC function by genetic ablation of the WRC components therefore alters dendritic spine structure and affects excitability [60][61][62] . CYFIP1 is highly enriched at synapses and its expression level is important for correct dendritic arborization and neuronal morphological complexity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3). Ablating the expression of Arp2/3 activators such as WAVE1 leads to aberrations in spine morphology as well as behavioral abnormalities (13,14). The Arp2/3 complex is essential for dendritic spine maintenance and function such as promoting the treadmilling of the actin cytoskeleton, morphological alterations in response to synaptic activity, and behavior (15,16).…”
Section: Dendritic Spine Actin Regulatorsmentioning
confidence: 99%